Supporting Children Experiencing Social and Emotional Needs Who are Identified By School Staff as At Risk of Exclusion Due to Disruptive Classroom Behavior - White, Robert (Journal of the American Academy of Special Education Professionals, 2024)
The positive promotion of social and emotional wellbeing in schools can be seen as a means to lessen the impact of social difficulties and behavioral problems on educational engagement. This study employed a multicomponent, whole school approach to promoting positive social and emotional wellbeing. School personnel identified nine primary Key Stage 2 pupils (ages 8 - 10) who were at risk of exclusion due to their disruptive and aggressive behavior. These pupils attended five maintained primary schools located across England. Following analysis of four baseline data points for stability, the Building Schools of Character (BSC) program was commenced. During this period, classroom observations were conducted weekly over the course of one academic school year. All pupils showed a marked decrease in disruptive behavior and were no longer considered at risk of exclusion by staff. These findings suggest a whole school positive social and emotional development approach can decrease disruptive behavior in the classroom.